Forming a High School basketball team based on motor educability and motor ability test - Maulidya Bintang Awwalina Zaenal; Ajeng Dian Purnamasari; Didik Rilastiyo Budi; Yudhi Teguh Pambudi; Arfin Deri Listiandi (Universitas Sriwijaya, 2025)
Research Problems: Selecting new basketball team members who have good technique, efficient movements, and excellent physical condition is a challenge, especially at the high school level when team regeneration is difficult after the graduation of the 12th grade. To obtain new members quickly and objectively, an appropriate selection method is needed. Research Objectives: This research aims to recommend the formation of a high school basketball team in Purwokerto through the screening of potential athletes based on motor educability and motor ability tests, to help coaches in building a new team and achieving maximum performance. Methods: Quantitative descriptive with ex-post facto research design, to determine an effective test for the formation of a basketball team. Assessment of Motor Educability using the IOW Brace Motor Educability Test instrument and Motor Ability using the Barrow Motor Ability Test Instrument. Results: Both tests provide measurable assessments to evaluate the potential of students to become basketball players. The positive correlation from the results of the motor educability and motor ability tests both support producing effective and efficient movements following the movements and components in basketball. Conclusion: The use of motor educability and motor ability tests can serve as an objective basis for recommendations in the formation of high school basketball teams. This test helps coaches in forming a team that not only has good physical abilities, but also the ability to learn and adapt quickly.